2016
DOI: 10.31699/ijcpe.2016.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Low Carbon Steel in Sulfuric Acid Using Polyvinyl Alcohol

Abstract: The inhibitive power of Polyvinyl Alcohol (PVA) was investigated toward the corrosion of carbon steel in 0.2N H2SO4 solution in the temperature range of 30-60˚C and PVA concentration range of 150-2000 ppm.    The corrosion rate was measured using both the weight loss and the electrochemical techniques. The weight loss results showed that PVA could serve as a corrosion inhibitor but its inhibition power was found to be low for the corrosion of carbon steel in the acidic media. Electrochemical analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In another study, this group of authors showed that partially hydrolyzed PVA (PVA-1) showed better performance for MS in 1M HCl than the fully hydrolyzed PVA (PVA-II) [87]. Other authors also described the %IE of PVA and its derivatives [88][89][90][91][92].…”
Section: Polyvinyl Alcohol (Pva) As Aqueous Phase Corrosion Inhibitormentioning
confidence: 99%
“…In another study, this group of authors showed that partially hydrolyzed PVA (PVA-1) showed better performance for MS in 1M HCl than the fully hydrolyzed PVA (PVA-II) [87]. Other authors also described the %IE of PVA and its derivatives [88][89][90][91][92].…”
Section: Polyvinyl Alcohol (Pva) As Aqueous Phase Corrosion Inhibitormentioning
confidence: 99%